Physiological and ionic changes in dwarf coconut seedlings irrigated with saline water - Lima,Breno L. de C. (2017)
ABSTRACT Salt-tolerant plants are important to cope with salinity and/or sodicity problems in semiarid regions. The dwarf coconut palm (Cocos nucifera L.) has emerged as a salt-tolerant crop once established. However, little is known about the mechanisms that contribute to the survival of coconut seedlings under salinity stress. This study aimed to evaluate the effect of saline water on morpho-physiological and biochemical responses of dwarf coconut seedlings. Treatments were composed of five levels of water salinity, expressed by its electrical conductivity (ECw), as follows: 0.9 (control); 5.2; 10.1; 15.3 and 19.3 dS m-1 in a completely randomized design with four replications. The high levels of organic solutes (carbohydrates and soluble amino-N) and Na+ in roots, that contribute to the low values of Na+/K+ ratio in the leaves, suggest that roots play an important role in the mechanism of salt tolerance of coconut seedlings. The use of brackish water with ECw of 5.2 dS m-1 allows seedling production, with no loss of quality. Based on total dry matter accumulation, seedlings were classified as moderately tolerant to the salinity of 10.1 dS m-1.